Proinflammatory interleukins 2, 6 and tumor necrosis factor alpha in patients with hypertension and diabetes mellitus depending on the presence of metabolic-associated liver steatosis - O.M. Radchenko; O.J. Komarytsia; M.O. Borovets; R.S. Ivasivka; R.R. Guta (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. Lack of information about proinflammatory interleukins (IL) and tumor necrosis factor alpha (TNFα) levels in case of metabolic-associated liver steatosis (MALS) and their roles in its progression to steatohepatitis are key reasons for the relevance and actuality of our study. The purpose: to evaluate proinflammatory interleukins 2, 6, and TNFα levels in concomitant liver steatosis. Materials and methods. Thirty-five patients with hypertension stage II–III, type 2 diabetes mellitus were examined. All of them were treated on an outpatient basis according to the guidelines of the Ministry of Health of Ukraine and the Declaration of Helsinki. Participants were divided into the main group with MALS (n = 24, males 45.8 %, females 54.2 %; average age 55.83 ± 0.89 years) and the control group without steatosis (n = 11, males 54.5 %, females 45.5 %; average age 53.00 ± 1.55 years). In addition to standard parameters, levels of IL6, IL2, TNFα, selectin, resistin, insulin, C-peptide, glycated hemoglobin, non-esterified fatty acids were evaluated, and some indexes were calculated, including triglyceride-glucose index and Castelli indexes I and II. Results were processed statistically, with significance level of р < 0.05. Results. Although MALS is not followed by qualitative differences in proinflammatory IL2, IL6 and TNFα compared to no steatosis, the risk of TNFα elevation was 5 times higher in patients with MALS (odds ratio 5.08; 95% confidence interval 1.02–25.17). An increase in IL2 and TNFα is unfavorable for patients with MALS, it can be considered as a marker of steatosis progression to steatohepatitis, as it is associated with transaminase activation, endogenous intoxication, lipid distress and glucose intolerance. IL6 was rather lower in patients with MALS compared to those without steatosis, but its growth was exponential and proceeded simultaneously to IL2 and TNFα. Conclusions. MALS was not associated with significant changes in IL2, IL6 and TNFα compared to no steatosis, but their elevation can be criteria for transformation into steatohepatitis due to the activation of transaminases, inflammation, endogenous intoxication, lipid distress, glucose intolerance.